PENGARUH BIAYA DISTRIBUSI TERHADAP JUMLAH PENJUALAN PUPUK PADA PT. PERTANI (PERSERO) CABANG BENGKULU - Rika Dwi Yulihartika (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2015)
Distribution represent the part activity of marketing which point to get correct goods and correct plance with efficient expense. Therefore distribution role of vital importance in aim peripatetic company is distribution area. PT. Pertani (Persero) on Bengkulu is peripatetic company of distribution fertilizer. Before sold to market, product sent from factory to distributor warehouse beforehand, afterwards in allocation to some region exist in province Bengkulu according to requirement of each region to distributed as according to request of market. Method research is referensi study and discipline study, in field study consist of observation and interview. Used by analysis method is analisys qualitative and quantitative. Quantitative analisys used whit statistical approach used simple linear regression formula and correlation coefficient analysis with person product moment method (r) and also to prove do there is relation and influence between distribution channel to purchase volume in thypothesis test (t-hitung> t-tabel).Result of analysis Y = 68.615 + 0,446 X meaning that constanta equal to 68.615 expressing that if influence from expense of physical distribution purchase volume equal 68.615. and regresi coefficient equal to 0,446 expressing that each addition 1 unit of physical distribution boosted up from purchase volume. Correlation coefficient (r) = 0,612, value positif correlation with purchase volume and physical distribution boosted. Value coefficient determination equal 0,374 is 37,4 % variable indenpenden of  purchase and variable dependen of physical distribution boosted, value 62,6% other of variabel on variable physical distribution boosted.Keywords : cost, physical distribution , distribution boosted